Religious studies route B Catholic Christianity and Judaism - Barron, Andrew; Cleary, Deirdre; Harrison, Patrick; White, Joy (Dynamic learning, 2017)
Help students to build their subject knowledge and understanding with this accessible and engaging Student's Book, created for the 2016 WJEC Eduqas GCSE (9-1) Religious Studies Route B specification by subject specialists with examining experience. - Feel confident teaching the Catholic and Judaism content with expert guidance written by faith experts and Diocesan advisors. - Develop understanding through clear, accessible explanations of the specification content and key concepts. - Keep track of progress with learning objectives and summaries for every topic. - Engage students and cement knowledge and skills using a range of assessment related tasks, activities and guidance that support learning and revision. - Cater for students of varying learning styles through a visually engaging approach that uses photos and artwork to enhance subject interest and understanding. To access draft content please log into www.wjecservices.co.uk. Your centre's unique login and username will be available from your Exams Officer. You will need permissions access to the 'Subject specific material including CPD' section.